2021
DOI: 10.3390/ijms22084261
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus and Maternal Immune Dysregulation: What We Know So Far

Abstract: Gestational diabetes mellitus (GDM) is an obstetric complication that affects approximately 5–10% of all pregnancies worldwide. GDM is defined as any degree of glucose intolerance with onset or first recognition during pregnancy, and is characterized by exaggerated insulin resistance, a condition which is already pronounced in healthy pregnancies. Maternal hyperglycaemia ensues, instigating a ‘glucose stress’ response and concurrent systemic inflammation. Previous findings have proposed that both placental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 186 publications
1
61
0
Order By: Relevance
“…190,191 It has been suggested that upregulation of circulating cytokines and altered frequencies of circulating immune cells may contribute to the development of GDM. 192 When compared to a healthy pregnancy, GDM was associated with an increased frequency of circulating CD14 + cells, yet a lower frequency of CD14 + CD16 + cells and monocytes and expression of TLR4, 193,194 a potential compensatory mechanism to limiting inflammation. 21 Additionally, increased levels of circulating soluble CD14 + have been reported with GDM.…”
Section: Metabolic Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…190,191 It has been suggested that upregulation of circulating cytokines and altered frequencies of circulating immune cells may contribute to the development of GDM. 192 When compared to a healthy pregnancy, GDM was associated with an increased frequency of circulating CD14 + cells, yet a lower frequency of CD14 + CD16 + cells and monocytes and expression of TLR4, 193,194 a potential compensatory mechanism to limiting inflammation. 21 Additionally, increased levels of circulating soluble CD14 + have been reported with GDM.…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…21 Additionally, increased levels of circulating soluble CD14 + have been reported with GDM. 193,194 It has been proposed…”
Section: Metabolic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus is a group of metabolic diseases characterized by hyperglycaemia that is divided into type I and type II. Recent studies have shown that long-term high glucose levels cause chronic damage to and dysfunction of several tissues, in particular the eyes, kidneys, heart, blood vessels, and nerves [ 7 , 8 ]. Diabetic nephropathy (DN) is the most common complication of diabetes and affects at least 30% of diabetic patients, representing great burden on public health [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Free mtDNA can trigger various inflammatory and apoptotic pathways once in the cytosol (Bronner & O'Riordan, 2016). Aberrant maternal immune cell adaption is related to GDM low-grade inflammation and poor fetal health outcomes (Kivelä et al, 2021;C. J. McElwain et al, 2021).…”
Section: Developmental Programming Of Cardiac Mitochondrial Biologymentioning
confidence: 99%